(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, the Possessor of Majesty and Honour. Praise be to Him for the bountiful blessings bestowed upon Him, and prayers and peace be upon the intercessor of the sinners on the Day of Crowds, and the leader of the deserters who are brought to the abode of peace, and upon his honorable family and companions, and after:The poem of Kaab bin Zuhair is considered one of the most famous poems in praise of the Holy Prophet (PBUH), which was known for its beginning (Bant Suad), and it is a wonderful masterpiece of Arabic poetry, and a unique artistic painting in its buildings and meanings. And its sciences, and it is from the poetry that was honored by the Messenger (PBUH) hearing it and turned a slave from anger to mercy, and to God is the role of Abu Ishaq Al-Ghazi who said: